The Rise and Role of AI Browser Agents in Modern Digital Workflows - Sankara Reddy Thamma (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
AI browser agents represent a significant advancement in the automation of web-based tasks by leveraging artificial intelligence to emulate human browsing behavior. These autonomous systems have demonstrated their utility across a wide range of domains, including e-commerce, healthcare, education, transportation, and customer service. By streamlining interactions with dynamic web content, AI browser agents enhance operational efficiency, personalize user experiences, and reduce manual effort. This article provides a comprehensive overview of the evolution and functionality of AI browser agents, examines their integration into industry-specific workflows, and explores the ethical, regulatory, and technical challenges associated with their deployment. Through practical examples and emerging use cases, we assess their transformative potential and outline the considerations necessary for responsible and scalable implementation.